Microbiological quality of drinking water in four communities in the Anangu Pitjantjatjara Lands, South Australia - Plazinska, Aleksandra; Australia. Bureau of Rural Sciences (Canberra : Bureau of Rural Sciences, 2000)
Report on microbiological aquifer contamination (2000) for human drinking water in four Central Australian Anangu Pitjantjatjara Lands communities (Ernabella, Fregon, Umuwa, Mimili); Results and Recommendations for up-grading and use of chlorine; detailed; maps, tables, figures.
Includes bibliographical references.
Keywords: Drinking water -- South Australia -- Testing; Drinking water -- Standards -- South Australia; Water supply - Ground water; Pitjantjatjara people (C6) (NT SG52-11); Water supply; Health; South Central Northern Territory (NT); Kaltjiti / Fregon (SA Central Australia SG53-09); Mimili / Everard Park (SA Central Australia SG53-13); South Australia - Central Australia (SA SG52, SG53); Pukatja / Ernabella (SA Central Australia SG53-09)